Tindak Tutur Ilokusi dalam Video Pembelajaran Geografi pada Kanal YouTube Ruang Guru - Ira Fazira; Fitriana Rahmadani Irma Anggraeni; Puspita Wijayanti; Trima Putri Nur Rahayu; Erna Hidayanti; Asep Purwo Yudi Utomo; Eko Ahmad Riyanto; Dina Aprilia; Mega Lusviyani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study examines illocutionary speech acts in geography learning on the Ruangguru YouTube channel, which has grown into one of the most popular online learning environments in Indonesia. The background of this study is the increasing use of digital media in the learning process, which requires teachers to develop effective communication strategies so that the material can be well understood by students. This study uses a qualitative descriptive approach that combines listening and note-taking methods. The research data consists of three videos on geography education: Definition of Geography, Geographical Conditions of the Asian Continent, and Concepts of Regions and Spatial Planning. Five categories of illocutionary speech acts, assertive, directive, expressive, commissive, and declarative, are clearly visible in the analysis based on Searle's (1975) classification. The most common category consists of assertive, followed by directive and expressive, while declarative and commissive are less dominant. Each type of speech act has a communicative purpose in the learning process by conveying information, encouraging involvement, expressing feelings, making promises, and establishing truth. The study's results indicate that illocutionary speech acts are crucial to creating engaging, interactive online learning. Practically, this research helps teachers and digital content creators improve communication strategies in online classes, while theoretically advancing pragmatic studies in the context of digital education.